Shaking table tests of a single-span freestanding rocking bridge for seismic resilience and isolation. Issue 15 (November 2019) - Du, Xiu-Li; Zhou, Yu-Long; Han, Qiang; Jia, Zhen-Lei
Rocking philosophy has advantages to maintain a preferable post-earthquake serviceability as an alternative of seismic resistant systems. This article presents an experimental study on the seismic behavior of a rocking bridge with freestanding columns capped with a freely supported deck. A 1/10 scaled, single-span double-column freestanding bridge was constructed and tested on a shaking table. The experimental results showed that the bridge model could undergo large rocking with enough stability under earthquakes and presented excellent post-earthquake resilience after earthquakes with limited damage and negligible residual displacement. The rocking bridge model also exhibited expected isolation efficiency, which increases as the level of excitations becomes more severe. In addition, an analytical model based on multi-block rocking mechanisms was used to calculate the displacement response. Compared with the experimental results, this analytical model well predicts the peak displacement of the rocking bridge model.